A Framework Based on Institutional Theory for Cyber Resiliency in County Government - Akech, Philip Otieno (JOOUST, 2020)
Cyber resiliency is the ability of a system to anticipate, withstand, recover and evolve when a cyber-attack has occuned in an organization or institution. Poor IT habits still persist in institutions exposing them to cyber-attacks as organizations are failing to enforce cybersecurity standards to adequately protect against threats. The increase in cyber-attacks occurring in organizations due to rapid changes in the technological environment has made organizations recognize the importance of resiliency as an enhancement to cyber security. Institutions such as the County governments which carry out their functions through computing infrastructure are highly predisposed to cyber-attacks due to the vast amount of information it has about the citizens. The purpose of the study was to develop a framework that would aid County governments become cyber resilient with Kakamega County government being the Case study. The objectives of the study were to determine the role of the county management and county employees in aiding cyber resiliency and to come up with a framework that would enhance cyber resiliency. The use of self-administered questionnaires involving 71 respondents drawn from. the 10 departments of the County government, was used as the research instrument to collect data. Data analysis was conducted using partial least square, structural equational modelling and the results did correspond to the institutional theory of how an institutional culture is formed with the county management and employees contributing to it and law having an intervening effect. The study's contribution was to policy making process by adding cyber resiliency as a construct of information security policy as attacks are increasingly being hard to safeguard completely against. With the study being carried out as a case study on one county, a wider random selection of counties would be recommended to have a representative idea of the whole country.